The power worshippers: inside the dangerous rise of religious nationalism - Stewart, Katherine (Bloomsbury Publishing, 2022)
Intro -- Half Title -- Dedication -- By the Same Author -- Title Page -- Contents -- Introduction -- 1. Church and Party in Unionville -- 2. Ministering to Power -- 3. Inventing Abortion -- 4. The Mind of a Warrior -- 5. Up from Slavery: The Ideological Origins of Christian Nationalism -- 6. The Uses and Abuses of History -- 7. The Blitz: Turning the States into Laboratories of Theocracy -- 8. Converting the Flock to Data -- 9. Proselytizers and Privatizers -- 10. Theocracy from the Bench, or How to Establish Religion in the Name of "Religious Liberty" -- 11. Controlling Bodies: What "Religious Liberty" Looks Like from the Stretcher -- 12. The Global Holy War Comes of Age -- Epilogue -- Acknowledgments -- Notes -- Index -- A Note on the Author -- Copyright.